BABIE LATO, WIĘC PORA UMIERAĆ? MECHANIZMY OSWAJANIA STAROŚCI WE WSPÓŁCZESNYM KINIE POLSKIM I CZESKIM - BATOR, MONIKA (Slavia Occidentalis, 2020)
The article is an attempt at presenting the similarities and differences in contemporary imaging of old age on the silver screen by using several examples of Polish and Czech (mostly) feature films from the 21st century. Special attention has been paid to the mechanisms of familiarising the taboo of passing away and old age in the cinematography of both countries.